Problem based learning and self-regulated learning: Impact on mathematical reasoning ability in the circle material - Pradini, Meysah Rani; Lusiana, Lusiana; Kesumawati, Nila (Desimal: Jurnal Matematika, 2022)
This research aims to see the effect of the problem-based learning model on mathematical reasoning abilities based on students' self-regulated learning on the circle material. The method used in this research is an experimental method (quantitative) with a  factorial design. The sampling technique in this research is cluster random sampling. Data collection techniques used in this research include tests to measure mathematical reasoning abilities and questionnaires to measure self-regulated learning. Based on the results of the research data analysis, it was concluded that there was an effect of the PBL model on students' mathematical reasoning abilities which was carried out through the overall final test and there were differences in the results of the reasoning ability tests and SRL given the PBL and conventional models. There are differences in mathematical reasoning abilities based on self-regulated learning, from the results of calculations using the two-way ANOVA test, while the interaction between the learning model and self-regulated learning of SMP Negeri 15 Palembang students is not found or there is no interaction.